2009
DOI: 10.4081/gh.2009.211
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal dynamics of global H5N1 outbreaks match bird migration patterns

Abstract: Abstract. The global spread of highly pathogenic avian influenza H5N1 in poultry, wild birds and humans, poses a significant pandemic threat and a serious public health risk. An efficient surveillance and disease control system relies on the understanding of the dispersion patterns and spreading mechanisms of the virus. A space-time cluster analysis of H5N1 outbreaks was used to identify spatio-temporal patterns at a global scale and over an extended period of time. Potential mechanisms explaining the spread o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
121
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(132 citation statements)
references
References 47 publications
9
121
0
2
Order By: Relevance
“…Although responses over large scales are well documented, with millions of animals adjusting the timing and routes of spectacular migrations to benefit from particular air or water currents (Jones et al 1979;Liechti et al 2000;Bohrer et al 2011), small-scale tactics have been documented in only a few instances (e.g., Wall et al 2006;Sapir et al 2011), primarily when the decreased costs of locomotion are visually obvious (Mandel and Bildstein 2007). Such widespread, nonrandom use of the environment across spatial scales is likely to have a profound effect on a range of population processes, from the formation of migratory flyways (Mandel et al 2008) to species distributions (Davies et al 2009), metapopulation dynamics, and the spread of disease (Si et al 2009). Quantification and visualization of energy landscapes could therefore provide insight into physical factors that affect these processes.…”
Section: Introductionmentioning
confidence: 99%
“…Although responses over large scales are well documented, with millions of animals adjusting the timing and routes of spectacular migrations to benefit from particular air or water currents (Jones et al 1979;Liechti et al 2000;Bohrer et al 2011), small-scale tactics have been documented in only a few instances (e.g., Wall et al 2006;Sapir et al 2011), primarily when the decreased costs of locomotion are visually obvious (Mandel and Bildstein 2007). Such widespread, nonrandom use of the environment across spatial scales is likely to have a profound effect on a range of population processes, from the formation of migratory flyways (Mandel et al 2008) to species distributions (Davies et al 2009), metapopulation dynamics, and the spread of disease (Si et al 2009). Quantification and visualization of energy landscapes could therefore provide insight into physical factors that affect these processes.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported temporal and spatial overlap between global H5N1 outbreaks and bird migration patterns (e.g. Gilbert et al 2006;Si et al 2009) and some species held under laboratory conditions have been seen to shed these viruses without overt clinical symptoms (Keawcharoen et al 2008). Yet most isolations of HPAI viruses in wild birds are from dead or moribund individuals, with only three reported cases of HPAI H5N1 from apparently healthy birds (Feare 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the global pattern of H5N1 is generally consistent with the major bird migration routes (Kilpatrick et al, 2006;Si et al, 2009), and H5N1 virus spread has been found to broadly match bird migration in the Western Paleartic (Gilbert et al, 2006). Experimental infection of swans and geese has revealed that these birds may shed H5N1 virus before the onset of clinical signs (Brown et al, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…In these ecological settings, hunting also may have a role in H5N1 transmission from wild birds to poultry, for example through disposal of offals in the backyard (Gill et al, 2006;Newman et al, 2008). Few H5N1 infections have been recorded in poultry in central and western parts of Europe, suggesting that perhaps here wild birds were the main actors (Si et al, 2009).…”
Section: Introductionmentioning
confidence: 99%